Brominated flame retardants - Eljarrat, Ethel; Barceló, Damià (The handbook of environmental chemistry, 2011)
Brominated flame retardants are one of the last classes of halogenated compounds that are still being produced worldwide and used in large quantities in many applications. They are used in plastics, textiles, electronic circuitry, and other materials to prevent fires. This volume covers the state-of-the-art of the analysis, fate and behaviour of brominated flame retardants. Experts in the field provide an overview of the compounds? physico-chemical properties and uses, their occurrence in the environment and biota, advanced chemical analytical methods, degradation studies, toxicological effects and human exposure. This book is a valuable and comprehensive source of information for environmental scientists interested in brominated flame retardant issues, and for authorities and producers